The Influence of Viral Marketing, Brand Awareness and Satisfaction on Purchasing Decisions of Nasa Beauty Product Customers: (Case Study on NASA Stockist R.508 Banjarnegara) - Davit Arifin; Bahtiar Efendi; Heri Purwanto; Muhammad Gilang Maulana Azka (Journal of Economics, Management, and Business, 2025)
Purpose - This study aims to analyze the influence of viral marketing, brand awareness, and customer satisfaction on purchasing decisions for NASA beauty products, with a case study at Stockist NASA R.508 Banjarnegara. Design/methodology/approach - This study uses a questionnaire as a data collection method with a sample of 114 respondents selected through the accidental sampling method. Respondents are customers who have made purchases at least three times at Stockist NASA R.508 Banjarnegara. The data used is primary data, with data analysis using multiple linear regression. Findings - This study explains that viral marketing, brand awareness, and customer satisfaction have a positive and significant influence on purchasing decisions for NASA beauty products. Viral marketing contributes to spreading product information widely and quickly through social media. Brand awareness helps increase customer trust and attraction to the product. Meanwhile, customer satisfaction strengthens loyalty and encourages repeat purchase decisions. Research limitations - Limitations rely on data collection through questionnaires, so there is a possibility that respondents provide answers that are very lacking in actual conditions. In addition, the scope of the study was limited to customers of NASA Stockist R.508 Banjarnegara, so the results may not be generalizable to all customers of NASA beauty products. Implications - The results of this study are expected to contribute to Stockist NASA R.508 Banjarnegara in increasing the effectiveness of marketing strategies, especially through the use of viral marketing, strengthening brand awareness, and increasing customer satisfaction to encourage purchasing decisions. In addition, this study can be a reference for similar businesses in designing more effective promotional strategies using digital platforms.